Stacking faults and the -surface on first-order pyramidal planes in -titanium. Issue 14 (13th May 2017) - Ready, A. J.; Haynes, P. D.; Rugg, D.; Sutton, A. P.
Abstract : Using first principles methods, we calculated the entire -surface of the first-order pyramidal planes in -titanium. Slip on these planes involving dislocations with -type Burgers vectors is one means by which -titanium polycrystals may supplement slip on prism planes with -type Burgers vectors to maintain ductility. We find one low energy and one high energy stacking fault with energies of 163 and 681 , respectively. Contrary to previous suggestions, we do not find a stable stable stacking fault at .